PEMANFAATAN KULIT KOPI ROBUSTA (COFFEA CANEPHORA) SEBAGAI ALTERNATIF PEMBUATAN PUPUK CAIR ORGANIK - Fachrurrozi Roseadi; Rafael Ferdinand S; Farhan Hamid; Denny Oktavina Radianto (Universitas Pahlawan Tuanku Tambusai, 2023)
Coffee skin is part of the coffee fruit which is on the outer layer. Coffee skin waste is mostly wasted without any initiative from the community to be reprocessed. If left too long in the ground this coffee skin will cause soil pollution. However, it turns out that this coffee skin can be used as organic liquid fertilizer. Coffee skin has a lot of nutrients in it. This study aims to determine the effectiveness of coffee skin in the manufacture of organic liquid fertilizer. The independent variable in this study was coffee skin, namely dry coffee skin. The dependent variable in this study is the quality of organic liquid fertilizer. While the control variables in this study were the influence of the soaking/fermentation time of the coffee skins for a period of 2 weeks, the influence of the temperature and humidity of the place and the influence of the characteristics of the coffee skins, namely the dry coffee skin and the Robusta type. The use of dry coffee skin is because coffee skin has a high nutrient content, so that plants that are given this liquid fertilizer thrive. The results showed that plants that were given this liquid fertilizer could thrive and grow faster than the use of other fertilizers. Keywords: Coffee skin, liquid fertilizer, organic